The more they spend, the more I earn? : Firms' training investments and post-training wages of apprentices - Dietrich, Hans [Verfasser]; Pfeifer, Harald [Verfasser]; Wenzelmann, Felix [Verfasser] (My University, 2016)
"In this paper, we examine the relation between a firm's training investment and the post-training wages of apprenticeship graduates. For our analysis, we first calculate a training investment indicator using detailed information about firm-level training costs. We then merge the firm-level data with individual-level administrative data on employment and wages of apprenticeship graduates. Using regression models controlling for selection into employment, we find that a firm investment in training relates positively with graduates' post-training wages. Doubling a firm's training investment leads to a wage mark-up of about 2.8%. This result is robust to different specifications. However, we find that especially graduates from low-investment firms benefit from a higher training investment. The wage mark-up for graduates from firms with already high investment levels is small and statistically not significant." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.1 Finanzierungsquellen; G 1.2.2.1 Lohn- & Tarifsysteme; Betriebliche Berufsausbildung; Ausbildungsinvestition; Einflussfaktor; Lohnhöhe; Ausbildungsabsolvent